Integrering av autopilotsystem och display för ruttstyrning av passagerarfärja - Integration of autopilot system and display for route control of a passenger ferry - Nordström, Pontus; Persson, Alice (My University, 2026)
This degree project has been carried out in collaboration with the company Cstrider AB to investigate the possibility of integrating a display with an autopilot system. The report presents the methodology used in the work as well as the results achieved. Cstrider AB is a company that aims to make it easier to commute over water and minimize the environmental impact by using small electrically powered passenger ferries. The work focuses on investigating the possibility of integrating a display with an autopilot system to reduce the number of displays in the ferry, as well as providing suggestions on how the integration should be implemented. The project developed a user-friendly interface for a display adapted for controlling an autopilot system. The interface enables an operator to select, start and cancel routes, as well as perform course corrections during the ferry’s journey. The communication between the display and the autopilot system is carried out via CAN using the communication standard NMEA 2000. The work resulted in a working structure for receiving messages via CAN, which enabled navigation information to be read, such as the ferry’s current heading. The transmission of messages via CAN was investigated but could not be verified and therefore resulted in a proposal for how it could be done. Detta examensarbete har genomförts i samarbete med företaget Cstrider AB för att undersöka möjligheten att integrera en display med ett autopilotsystem. Rapporten redovisar den metodik som använts i arbetet samt de resultat som uppnåtts. Cstrider AB är ett företag som vill göra det lättare att pendla över vattnet och minimera klimatpåverkan genom att använda mindre eldrivna passagerarfärjor. Arbetet fokuserar på att undersöka möjligheten att integrera en display med ett autopilotsystem för att reducera antalet skärmar i färjan, samt ge förslag på hur en integration bör kunna genomföras. Under arbetet utvecklades ett användarvänligt användargränssnitt för en display som är anpassat för styrning av ett autopilotsystem. Gränssnittet gör det möjligt för operatören att välja, starta och avbryta rutter, samt utföra kurskorrigeringar under färjans färd. Kommunikationen mellan displayen och autopilotsystemet sker via CAN med kommunikationsstandarden NMEA 2000. Arbetet resulterade i en fungerande struktur för mottagning av meddelanden via CAN som möjliggjorde avläsning av navigationsinformation, exempelvis färjans aktuella kurs. Sändning av meddelanden via CAN undersöktes men kunde inte verifieras utan resulterade i ett förslag på hur det kan genomföras.
Keywords: Integrering, systemintegration, CAN, NMEA 2000, autopilotsystem, Raymarine, display, ifm, passagerartransport